Macrophage metalloelastase (MMP-12) deficiency does not alter bleomycin-induced pulmonary fibrosis in mice - Boichot Elisabeth; Guenon Isabelle; Nenan Soazig; Manoury Boris; Planquois Jean-Michel; Bertrand Claude P; Lagente Vincent (BMC, 2006)
Abstract Background Pulmonary fibrosis is characterized by excessive deposition of extracellular matrix in the interstitium resulting in respiratory failure. The role of remodeling mediators such as metalloproteinases (MMPs) and their inhibitors (TIMPs) in the fibrogenic process remains misunderstood. In particular, macrophage metalloelastase, also identified as MMP-12, is known to be involved in remodeling processes under pathological conditions. However, MMP-12 involvement in pulmonary fibrosis is unknown. Here we investigated fibrotic response to bleomycin in MMP-12 deficient mice. Materials and methods C57BL/6 mice, Balb/c mice and MMP-12 -/- mice with a C57BL/6 background received 0.3 mg bleomycin by intranasal administration. 14 days after, mice were anesthetized and underwent either bronchoalveolear lavage (BAL) or lung removal. Collagen deposition in lung tissue was determined by Sircol™ collagen assay, MMP activity in BAL fluid was analyzed by zymography, and other mediators were quantified in BAL fluid by ELISA. Real time PCR was performed to assess gene expression in lung removed one or 14 days after bleomycin administration. Student t test or Mann & Whitney tests were used when appropriate for statistical analysis. Results The development of pulmonary fibrosis in "fibrosis prone" (C57BL/6) mice was associated with prominent MMP-12 expression in lung, whereas MMP-12 expression was weak in lung tissue of "fibrosis resistant" (Balb/c) mice. MMP-12 mRNA was not detected in MMP-12 -/- mice, in conformity with their genotype. Bleomycin elicited macrophage accumulation in BAL of MMP-12 -/- and wild type (WT) mice, and MMP-12 deficiency had no significant effect on BAL cells composition. Collagen content of lung was increased similarly in MMP-12 -/- and WT mice 14 days after bleomycin administration. Bleomycin elicit a raise of TGF-β protein, MMP-2 and TIMP-1 protein and mRNA in BAL fluids and lung respectively, and no significant difference was observed between MMP-12 -/- and WT mice considering those parameters. Conclusion The present study shows that MMP-12 deficiency has no significant effect on bleomycin-induced fibrosis.